2017
DOI: 10.1186/s12889-017-4389-2
|View full text |Cite
|
Sign up to set email alerts
|

Anxiety and depression symptoms and alcohol use among adolescents - a cross sectional study of Norwegian secondary school students

Abstract: BackgroundWe investigated the associations between symptoms of anxiety and depression and alcohol drinking behavior among adolescents, by focusing on the importance of symptom load, as well as gender differences.MethodsData was derived from a cross-sectional school based survey among adolescents in upper secondary schools in Norway. Among other variables adolescents reported on symptoms of anxiety and depression, time of onset and extent of alcohol use. The sample consisted of 6238 adolescents aged 16–18 years… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
52
1
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 88 publications
(69 citation statements)
references
References 27 publications
8
52
1
3
Order By: Relevance
“…In this study, students who felt hopeless or sad were more likely to consume alcohol than their hopeful and happy counterparts. Similar findings were reported in previous studies [30][31][32][33][34]. Hopelessness is highly relevant condition that could motivate someone to consume alcohol [30].…”
Section: Discussionsupporting
confidence: 90%
“…In this study, students who felt hopeless or sad were more likely to consume alcohol than their hopeful and happy counterparts. Similar findings were reported in previous studies [30][31][32][33][34]. Hopelessness is highly relevant condition that could motivate someone to consume alcohol [30].…”
Section: Discussionsupporting
confidence: 90%
“…Similarly, another study conducted in Australia [37] showed that those who consumed alcohol were more likely to develop psychological distress. A study conducted in Norway [38] revealed that depression in adolescents was associated with the onset of alcohol consumption and that alcohol increased the risk of depression. This might be because high levels of alcohol consumption cause negative effects in many aspects of life, and it can also harm the brain, causing depression [39].…”
Section: Discussionmentioning
confidence: 99%
“…vímuefnaneyslan getur orsakað depurð og öfugt. Hvort sem veldur upphaf lega skiptir minna máli en sú staðreynd að þarna á milli getur myndast vítahringur sífellt meiri neyslu og verri líðunar sem hefur mikil áhrif á framtíðarheilsu ( Johannessen, Andersson, Bjorngaard og Pape, 2017). Það er hins vegar ljóst að jafnvel þó vímuefnaneysla hafi tengsl við depurð á meðal íslenskra unglinga, þá getur hún ekki skýrt aukninguna í depurð, því verulega hefur dregið úr henni á síðastliðnum árum (Arnarsson, Kristofersson og Bjarnason, 2018).…”
Section: Umraeðaunclassified